Partisipasi Masyarakat Dalam Konservasi Penyu (Chelonioidea) di Desa Riabao dan Desa Duawutun Kecamatan Nagawutung Kabupaten Lembata - Sofian Syukur; Saryono Yohanes; Herinimus Ratu Udju (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Conservation is one of the ways taken by the government to protect, conserve, and maintain biodiversity and its ecosystems from extinction. So that the provisions of Article 21 paragraph 2 of Law no.5 of 1990 concerning the Conservation of Natural Resources and Their Ecosystems are expressly regulated regarding the prohibition of trading and utilizing protected animals, including eggs and other parts. Poaching, turtle egg theft, and coastal pollution are some of the factors that cause the drastic decline in the population of these rare animals. One of the turtle conservation places in Lembata Regency is the Loang Turtle Conservation. This research is an empirical juridical research, namely reviewing and analyzing the turtle conservation process by the people of Riabao Village and Duawutun Village, and knowing the participation of the people of Riabao Village and Duawutun Village in turtle conservation efforts. By using a special approach and approach to legislation that examines the conformity between the applicable legal provisions and the facts that occur in the field. The results of this study show that: (1) Apart from the declining population and government policy attachment related to the prohibition of turtle hunting, another major factor in the establishment of this captivity geographically is because the Loang coastline is the destination area for the migration of turtles. (2) Community participation in conservation efforts of turtles as protected animals on the coast of Loang, Riabao Village and Duawutun Village, Nagawutung District, Lembata Regency, which was initially a group of conservation youth who felt very concerned about the survival of the ancient animal.